The jagged edge of duty a fighter pilot's World War II - Richardson, Robert L. 1949- (Stackpole Books, 2017)
"The World War II fighter-pilot story. On the very first day of the invasion of Sicily, three months into his combat career, Allan Knepper flew his P-38 Lightning fighter in a squadron sent out to sweep the island and interdict German ground targets. Retreating German infantry unexpectedly pounded the American flyers. Knepper was one of two shot down; he was never found. Knepper's story is the story-in-microcosm of thousands of American fighter pilots in World War II. Richardson recounts Knepper's experiences from training through combat and uses them to discuss the aircraft, tactics and doctrine, training, base life, and aerial combat of the war. This is the intimate account of one pilot at war, but also the anatomy of the fighter-pilot experience in World War II."...Provided by publisher
Includes bibliographical references and index
Keywords: Knepper, Alan -- 1916-1943; United States -- Army Air Forces -- Fighter Squadron, 49th -- Biography; Geschichte 1943; Weltkrieg (1939-1945); Fighter pilots -- United States -- Biography; Lightning (Fighter plane) -- Anecdotes; World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Campaigns -- Italy; World War, 1939-1945 -- Africa, North; World War, 1939-1945 -- Regimental histories -- United States; Invasion; Luftwaffe; Zweiter Weltkrieg; Italien; USA; Sizilien; Amerika; Biografie